Unsystematic Risk over Time - Mokkelbost, Per B. (Journal of Financial and Quantitative Analysis, 1971)
Articles by Sharpe [1], Lintner [2], and Hastie [3] introduce concepts of systematic and unsystematic risk associated with portfolio rate of return. Defining risk as variation in portfolio return, such risk comprises two elements:1. Systematic risk or variation, which is the covariation of portfolio rate of return with market rate of return.2. Unsystematic risk or variation, which is the difference between total portfolio variation and systematic variation. Unsystematic variation is therefore variation due to attributes of individual securities.